Fiber-reinforced resin composition with improved defibration properties, its manufacturing method, molded body, and defibration agent
Patent Information
- Application Number
- JP2022503676
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-02-26
- Filing Date
- 2021-02-25
- Publication Date
- 2025-01-08
- Estimated Expiration
- 2041-02-25
AI Technical Summary
【0016】 本発明に使用される解繊剤(B1)は、化学修飾により疎水化されたセルロース系繊維集合体の解繊を促進することができるので、解繊剤(B1)を使用して解繊原料からミクロフィブリル化された疎水化セルロース系繊維(A)を容易に得ることができる。
Smart Images

Figure 0007610210000005 
Figure 0007610210000006 
Figure 0007610210000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a fiber-reinforced resin composition and a production method thereof, as well as a molded body and a defibrating agent. [Background technology]
[0002] Microfibrillated cellulose fibers (sometimes referred to herein as MFC, cellulose nanofibers, or CNF) are made by defibrating plant fibers or paper pulp to micro- or nano-level thicknesses, and are lightweight and strong.
[0003] Research is being conducted into improving the inherent properties of resins, such as strength properties, by compounding MFC with resin. In such research, since the strength properties of a composite containing fiber and resin are highly dependent on the thickness of the fibers contained in the resin, or the affinity between the fiber and resin and the dispersibility of the fiber in the resin, methods such as the following have been disclosed, which involve subjecting a cellulosic fiber assembly to a defibration treatment to form microfibrillations, and chemically modifying MFC to make it hydrophobic in order to improve its affinity with and dispersibility in the resin to be compounded:
[0004] Patent Documents 1 and 2 disclose a method for producing an aliphatic polyester composition by melt-kneading a resin component consisting of an aliphatic polyester and polylactic acid, and a fiber component consisting of pretreated pulp and / or cellulosic fibers in which the primary wall and the outer layer of the secondary wall have been damaged, in the presence of a cellulose amorphous region swelling agent such as water, ethylene glycol, or butylene glycol, and state that the fiber component is defibrated and microfibrillated during the melt-kneading.
[0005] Patent Document 3 discloses a method for producing cellulose nanofibers by stirring at high speed a mixture of a plant-derived fiber assembly with a lignin content of 0 to 5% by weight and a wide variety of liquid substances. As one of the wide variety of liquid substances used, a hydrocarbon having 3 to 20 carbon atoms that may contain heteroatoms is disclosed, and among them, ethylene glycol and diethylene glycol are described.
[0006] Patent Document 4 discloses a method for producing a fine cellulose fiber dispersion containing fine cellulose fibers, at least one of a resin and a resin precursor, and an organic solvent by defibrating the cellulose fibers in a dispersion containing cellulose fibers, at least one of a resin and a resin precursor, and a wide variety of organic solvents (aromatic hydrocarbons, aprotic polar solvents, alcohol solvents, ketone solvents, glycol ether solvents, halogenated solvents, etc.) using a bead mill, high-pressure homogenizer, etc. Examples of glycol ether solvents include ethylene glycol monomethyl ether and propylene glycol monomethyl ether.
[0007] Patent Document 5 discloses a method for producing a fine cellulose fiber dispersion containing fine cellulose fibers, at least one of a resin and a resin precursor, and an organic solvent, by defibrating the cellulose fibers in a dispersion containing cellulose fibers dispersed in a wide variety of organic solvents (single or mixed solvents such as aromatic hydrocarbons, aprotic polar solvents, alcohol solvents, ketone solvents, ether solvents, and glycol ether solvents) having a specific viscosity (1.0 mPa·S or more) and refractive index (1.40 or more) using a bead mill, high-pressure homogenizer, or the like.
[0008] Patent Document 6 discloses a method for producing a composition containing chemically modified CNF and a thermoplastic resin, in which specific chemically modified cellulose fibers are melt-kneaded with a thermoplastic resin while the chemically modified cellulose fibers are defibrated in the molten mixture.
[0009] Patent Document 7 discloses a defibrating aid for hydrophobic cellulose-based fibers, which is made of a specific amide, a method for producing a resin composition containing a hydrophobic MFC using the same, and a molded product. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] JP 2005-42283 A [Patent Document 2] JP 2007-262649 A [Patent Document 3] JP 2010-216021 A [Patent Document 4] International Publication No. 2011 / 125801 [Patent Document 5] JP 2013-36035 A [Patent Document 6] JP 2016-176052 A [Patent Document 7] International Publication No. 2019 / 163873 Summary of the Invention [Problem to be solved by the invention]
[0011] The object of the present invention is to provide a fiber-reinforced resin composition (D) containing microfibrillated hydrophobic cellulosic fibers (A), a defibrating agent (B1) and a thermoplastic resin (C), and optionally a defibrating agent (B2); an efficient method for producing the same; a defibrating agent excellent in defibrating a hydrophobic cellulosic fiber aggregate (AP); and a fiber-reinforced molded article made of the resin composition and having excellent mechanical properties (particularly strength properties and toughness). [Means for solving the problem]
[0012] The present inventors have discovered that when a mixture of a cellulose-based fiber assembly that has been modified with a specific chemical modifying group to make it hydrophobic (hereinafter also referred to as a hydrophobic cellulose-based fiber assembly or a defibrating raw material) and a thermoplastic resin is melt-kneaded in the presence of a polyhydric alcohol or lactone of a specific molecular weight (hereinafter also referred to as a defibrating agent (B1)), defibration of the cellulose-based fiber assembly is promoted during melt-kneading, and a thermoplastic resin composition containing microfibrillated hydrophobic cellulose fibers is obtained.
[0013] That is, it has been found that a polyhydric alcohol or lactone having a specific molecular weight acts as a defibration promoter (defibration agent) for an assembly of hydrophobized cellulose-based fibers. The present invention has been completed based on this finding.
[0014] The present invention relates to a fiber-reinforced resin composition, a molded body, and a method for producing a fiber-reinforced resin composition described in the following items.
[0015] Section 1. A fiber-reinforced resin composition (D) containing microfibrillated hydrophobized cellulosic fibers (A), a defibrating agent (B1), and a thermoplastic resin (C), The microfibrillated hydrophobic cellulosic fibers (A) are modified with an acyl group having 2 to 5 carbon atoms, The defibrating agent (B1) is at least one compound selected from the group consisting of polyhydric alcohols having a molecular weight of 130 to 400 and lactones having a molecular weight of 86 to 115. Resin composition (D). Section 2. The fiber-reinforced resin composition (D) further contains a defibrating agent (B2), Item 2. The fiber-reinforced resin composition according to Item 1, wherein the defibrating agent (B2) is at least one selected from the group consisting of talc, clay, zeolite, aluminum oxide, calcium carbonate, titanium oxide, silica, magnesium oxide, and mica. Section 3. Item 3. The fiber-reinforced resin composition according to item 1 or 2, wherein the defibrating agent (B1) is at least one selected from the group consisting of dipropylene glycol, triethylene glycol, diglycerol, tripropylene glycol, tetraethylene glycol, polyethylene glycol (number average molecular weight 200 to 400), polyoxypropylene glycol (number average molecular weight 200 to 400), polyoxypropylene glyceryl ether (number average molecular weight 200 to 400), δ-valerolactone, and ε-caprolactone. Section 4. Item 3. The fiber-reinforced resin composition according to Item 1 or 2, wherein the microfibrillated hydrophobic cellulose-based fibers (A) are modified with an acetyl group, and the defibrating agent (B1) is at least one selected from the group consisting of dipropylene glycol, tripropylene glycol, polyoxypropylene glycol (average molecular weight 200), polyoxypropylene glyceryl ether (average molecular weight 250), δ-valerolactone, and ε-caprolactone. Section 5. 5. The fiber-reinforced resin composition according to any one of items 1 to 4, wherein the thermoplastic resin (C) is at least one selected from the group consisting of polyamide, polyolefin, aliphatic polyester, aromatic polyester, polyacetal, polycarbonate, polyvinyl chloride, polystyrene, acrylonitrile-butadiene-styrene copolymer (ABS resin), styrene-butadiene block copolymer, polycarbonate-ABS alloy (PC-ABS alloy) and modified polyphenylene ether (m-PPE). Section 6. Item 6. The fiber-reinforced resin composition according to item 5, wherein the polyolefin is at least one selected from the group consisting of polypropylene, polyethylene, a polypropylene copolymer, and a polyethylene copolymer. Section 7. Item 7. The fiber-reinforced resin composition according to any one of Items 1 to 6, wherein the microfibrillated hydrophobized cellulosic fibers (A) are microfibrillated hydrophobized lignocellulosic fibers (MFLC). Section 8. 8. The fiber-reinforced resin composition according to any one of Items 1 to 7, wherein the content of the defibrating agent (B1) is 0.001 to 2% by mass based on the total mass of the fiber-reinforced resin composition. Section 9. Item 9. A molded article made of the fiber-reinforced resin composition according to item 8. Section 10. The method includes a step of mixing a hydrophobized cellulose fiber assembly (AP) modified with an acyl group having 2 to 5 carbon atoms, a defibrating agent (B1) and a thermoplastic resin (C), and defibrating the hydrophobized cellulose fiber assembly (AP) during the mixing operation to form microfibrils. A method for producing a fiber-reinforced resin composition (D) containing microfibrillated hydrophobized cellulosic fibers (A) and a thermoplastic resin (C), comprising: The microfibrillated hydrophobic cellulosic fibers (A) are modified with an acyl group having 2 to 5 carbon atoms, The defibrating agent (B1) is at least one compound selected from the group consisting of polyhydric alcohols having a molecular weight of 130 to 400 and lactones having a molecular weight of 86 to 115. A method for producing a fiber-reinforced resin composition (D). Section 11. Item 11. The production method according to Item 10, wherein a defibrating agent (B2) is further mixed in the step to produce a fiber-reinforced resin composition (D) further containing a defibrating agent (B2), wherein the defibrating agent (B2) is at least one selected from the group consisting of talc, clay, zeolite, aluminum oxide, calcium carbonate, titanium oxide, silica, magnesium oxide, and mica. Section 12. (1) a first step of mixing a hydrophobized cellulose fiber assembly (AP) modified with an acyl group having 2 to 5 carbon atoms, a defibrating agent (B1) and a thermoplastic resin (C) and defibrating the hydrophobized cellulose fiber assembly (AP) during the mixing operation to form microfibrils; (2) a second step of removing the defibrating agent (B1) from the mixture obtained in the first step, which contains the microfibrillated hydrophobized cellulosic fibers (A), the defibrating agent (B1), and the thermoplastic resin (C); A method for producing a fiber-reinforced resin composition (D) containing microfibrillated hydrophobized cellulosic fibers (A) and a thermoplastic resin (C), comprising: The microfibrillated hydrophobic cellulosic fibers (A) are modified with an acyl group having 2 to 5 carbon atoms, The defibrating agent (B1) is at least one compound selected from the group consisting of polyhydric alcohols having a molecular weight of 130 to 400 and lactones having a molecular weight of 86 to 115. A method for producing a fiber-reinforced resin composition (D). Section 13. Item 13. The production method according to Item 12, wherein a fiber-reinforced resin composition (D) further containing a defibrating agent (B2) is produced by further mixing a defibrating agent (B2) in the first step, wherein the defibrating agent (B2) is at least one selected from the group consisting of talc, clay, zeolite, aluminum oxide, calcium carbonate, titanium oxide, silica, magnesium oxide, and mica. Section 14. A method for producing a fiber-reinforced resin composition (D) containing microfibrillated hydrophobized cellulosic fibers (A), a thermoplastic resin (C), and a compatibilizer (E), or containing microfibrillated hydrophobized cellulosic fibers (A), a defibrating agent (B2), a thermoplastic resin (C), and a compatibilizer (E), wherein a compatibilizer (E) is further mixed in the step of item 10 or 11 or the first step of item 12 or 13. Section 15. Item 10 to Item 14, wherein the thermoplastic resin is at least one selected from the group consisting of polyamide, polyolefin, aliphatic polyester, aromatic polyester, polyacetal, polycarbonate, polystyrene, acrylonitrile-butadiene-styrene copolymer (ABS resin), polycarbonate-ABS alloy (PC-ABS alloy) and modified polyphenylene ether (m-PPE). The method for producing the fiber-reinforced resin composition (D) according to any one of Items 10 to 14. Section 16. A defibrating agent for defibrating an assembly of hydrophobic cellulose-based fibers modified with an acyl group having 2 to 5 carbon atoms, the defibrating agent comprising at least one compound selected from the group consisting of polyhydric alcohols having a molecular weight of 130 to 400 and lactones having a molecular weight of 86 to 115. Section 17. Item 17. The defibrating agent according to Item 16, wherein the compound is at least one selected from the group consisting of dipropylene glycol, triethylene glycol, diglycerol, tripropylene glycol, tetraethylene glycol, polyethylene glycol (number average molecular weight 200 to 400), polyoxypropylene glycol (number average molecular weight 200 to 400), polyoxypropylene glyceryl ether (number average molecular weight 200 to 400), δ-valerolactone, and ε-caprolactone. Effect of the Invention
[0016] The defibrating agent (B1) used in the present invention can promote the defibration of a cellulosic fiber assembly that has been hydrophobized by chemical modification, and therefore, using the defibrating agent (B1) can easily produce microfibrillated hydrophobic cellulosic fibers (A) from the defibrated raw material.
[0017] Hereinafter, this microfibrillated hydrophobized cellulosic fiber (A) is also referred to as hydrophobized MFC.
[0018] The hydrophobized MFC has a high affinity with thermoplastic resins because it is hydrophobized by a specific hydrophobic chemical modification group. Therefore, the hydrophobized MFC can be easily mixed with thermoplastic resins and dispersed uniformly or nearly uniformly in a fine state in a melt-kneaded composition (e.g., a fiber-reinforced resin composition). As a result, a molded article made of the fiber-reinforced resin composition of the present invention has excellent mechanical properties (strength properties and toughness).
[0019] Furthermore, in the production method of the present invention, by having the defibrating agent (B1) present during melt-kneading of the hydrophobized cellulose-based fiber aggregate and the thermoplastic resin, the hydrophobized cellulose-based fiber aggregate is easily microfibrillated during melt-kneading, so that a melt-kneaded product containing the hydrophobized MFC (i.e., the fiber-reinforced resin composition of the present invention) can be efficiently produced. [Brief description of the drawings]
[0020] [Figure 1] 1 is an electron microscope image of acetylated unbleached pulp derived from Abies sachalinensis used as a defibrating raw material for the composition of Example 6. [Diagram 2] 1 is an electron microscope image of acetylated fir fibers in a sample prepared from the composition of Example 6. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] 1. Explanation of terms and abbreviations As used herein, the following terms have the following meanings:
[0022] Cellulosic fibres refer to fibres containing cellulose and / or lignocellulose of plant, microbial, algae or tunicates (ascidians).
[0023] Lignocellulose is a complex hydrocarbon polymer (a mixture of natural polymers) that constitutes the cell walls of trees, and is known to be composed mainly of the polysaccharides cellulose and hemicellulose, and the aromatic polymer lignin. In the present invention, lignocellulose means a substance composed of cellulose, hemicellulose, and lignin, regardless of the amount of lignin content and regardless of the presence or absence of chemical bonds between the cellulose, hemicellulose, and / or lignin.
[0024] Cellulosic pulp refers to a fiber assembly made of cellulose-based polymers. Cellulosic pulp (CP) includes pulp that does not contain lignin (pulp made of cellulose, pulp made of holocellulose, etc.) and pulp that contains lignin (lignopulp). Cellulosic pulp is also classified according to its origin as follows: cellulosic fiber assembly (plant-derived pulp) isolated from the whole plant or part of a plant such as wood, bamboo, rice straw, cotton, etc.; cellulosic fiber assembly (microorganism-derived pulp) isolated from a mixture of cellulose produced by microorganisms and microbial cells; cellulosic fiber assembly (algae-derived pulp) isolated from algae; and cellulosic fiber assembly (sea squirt-derived pulp) isolated from tunicates (squirt-derived pulp).
[0025] In this specification, cellulosic pulp may be collectively referred to as "pulp."
[0026] Lignopulp means pulp containing lignocellulose.
[0027] The hydrophobized cellulose fiber assembly means pulp chemically modified with a hydrophobic group (e.g., an acyl group). In this specification, "chemical modification" means that a substituent (a chemically modified group) is introduced in place of the hydrogen atom of the hydroxyl group of the sugar chain constituting the cellulose fiber (the hydroxyl group is chemically modified). Thus, the hydrophobized cellulose fiber assembly is one embodiment of chemically modified pulp (chemically modified cellulose fiber assembly). Examples of the substituent include a hydrophobic group, for example, an acyl group, and preferably an acyl group having 2 to 5 carbon atoms. A preferred embodiment of the chemical modification is acylation, and a more preferred embodiment is acylation with an acyl group having 2 to 5 carbon atoms.
[0028] Chemically modified microfibrillated cellulose fibers (chemically modified MFC) refer to cellulose fibers that have been chemically modified and microfibrillated. A preferred chemically modified MFC is a hydrophobic MFC (microfibrillated hydrophobic cellulose fiber (A)), that is, a cellulose fiber that has been microfibrillated and has an acyl group having 2 to 5 carbon atoms introduced therein.
[0029] In this specification, microfibrillation means that the diameter of the fiber is on the nano order, or that the fibers present inside or on the surface of the fiber are on the nano order. Therefore, fibers whose diameter has been defibrated to the nano order, fibers whose diameter at the thickest part is on the nano order or larger (for example, several μm) but whose inside or surface has been defibrated to the nano order, and fibers that are a mixture of these fibers are also considered to be microfibrillated fibers.
[0030] The composite means a composition containing a matrix and something other than the matrix. When a resin is used as the matrix and fibers are used as the other, it is called a resin-fiber composite (or a fiber-resin composite), and may also be called a resin composite or a fiber composite. A specific fiber name may be used for the fiber, and a specific polymer name (a proper name of the resin, or a general name for resins such as thermoplastic resin) may be used for the resin. Therefore, a composition containing a thermoplastic resin as a matrix and a chemically modified MFC may be referred to as a thermoplastic resin-chemically modified MFC composite, a chemically modified MFC-thermoplastic resin composite, or a chemically modified MFC-containing thermoplastic resin composition, or may simply be referred to as a thermoplastic resin composite, a chemically modified MFC composite, or a composite. In the production of the composition according to the present invention, kneading or mixing the resin with the chemically modified MFC, the chemically modified cellulose-based fiber, or the chemically modified cellulose-based fiber aggregate (chemically modified pulp) is also called "composite formation".
[0031] The following abbreviations used in this specification have the following meanings: Acyl: Acyl group Ac: Acetyl group LP: Lignopulp CP: Cellulosic fiber aggregate (cellulosic pulp) AcCP: A pulp in which the hydrogen atoms of some of the hydroxyl groups in the sugar chains that compose the cellulose fibers of a cellulose fiber assembly (cellulose pulp), or in the sugar chains and lignin, are replaced with acetyl groups. AcLP: Lignopulp in which the hydrogen atoms of some of the hydroxyl groups in the sugar chains that make up the cellulosic fibers in lignopulp, or in the sugar chains and lignin, are replaced with acetyl groups. MFC: Microfibrillated cellulosic fibres AcylMFC: Cellulosic fiber in which some of the hydrogen atoms of the hydroxyl groups in the sugar chains or sugar chains and lignin that make up the fiber have been replaced with acyl groups and the fiber has been microfibrillated. AcMFC: Cellulosic fiber in which some of the hydrogen atoms of the hydroxyl groups in the sugar chains or sugar chains and lignin that make up the cellulosic fiber have been replaced with acetyl groups and microfibrillated. MFLC: Microfibrillated lignocellulosic fibers AcMFLC: Lignocellulosic fibers in which the hydrogen atoms of some of the hydroxyl groups in the sugar chains or sugar chains and lignin that make up the lignocellulosic fibers have been replaced with acetyl groups and microfibrillated.
[0032] 2. Defibrator The defibrating agent (B1) used in the present invention is at least one compound selected from polyhydric alcohols having a molecular weight of 130-400 and lactones having a molecular weight of 86-115.
[0033] The molecular weight of the defibrating agent (B1) in this specification refers to the molecular weight of that compound when it is a single compound, and refers to the number average molecular weight of that mixture when it is a mixture of polymers or oligomers.
[0034] The above polyhydric alcohols can be used alone or in combination of two or more kinds.
[0035] The polyhydric alcohol of the defibrating agent (B1) is preferably a polypropylene glycol-based diol (hereinafter also referred to as a "PPG-based diol"). Examples of PPG-based diols include dipropylene glycol, tripropylene glycol, polyoxypropylene glycol with a number average molecular weight of 200, polyoxypropylene glycol with a number average molecular weight of 400, polyether polyols obtained by addition polymerization of propylene oxide (hereinafter also referred to as "PO") to a dihydric alcohol, and polyether polyols obtained by addition polymerization of PO and an alkylene oxide other than PO (such as ethylene oxide (hereinafter also referred to as "EO")). The addition polymerization of PO and another alkylene oxide may be random addition polymerization or block addition polymerization.
[0036] Examples of the dihydric alcohol include dihydric alcohols having 2 to 4 carbon atoms, such as ethylene glycol, propylene glycol, 1,3-butanediol, and 1,4-butanediol. PPG diols have structural isomers depending on the mode of addition polymerization of PO, and the PPG diols referred to in this specification include each of these isomers and mixtures thereof. The molecular weight of the PPG diol is preferably 130-400, more preferably 130-350, further preferably 130-300, and particularly preferably 150-250.
[0037] The polyhydric alcohol of the defibrating agent (B1) is preferably an addition polymer of ethylene oxide (EO) (an addition polymer of 3 to 8 EO units) having a molecular weight of 130 to 400. Examples of the addition polymer of EO include triethylene glycol, tetraethylene glycol, pentaethylene glycol, hexaethylene glycol, octaethylene glycol, and mixtures thereof. A mixture of EO addition polymers having a number average molecular weight of 200 is called PEG200, and a mixture having a number average molecular weight of 400 is called PEG400.
[0038] As the polyhydric alcohol of the defibrating agent (B1), a glycerin derivative having a molecular weight of 130 to 400 and a mixture of glycerin derivatives can also be used. Specific examples of these glycerin derivatives include a dimer of glycerin (diglycerol) and a product obtained by addition polymerization of PO with glycerin (polyoxypropylene glyceryl ether). Polyoxypropylene glyceryl ether has structural isomers depending on the addition polymerization mode of PO, and the polyoxypropylene glyceryl ether referred to in this specification also includes the structural isomers and mixtures thereof. A preferred polyoxypropylene glyceryl ether is polyoxypropylene glyceryl ether (number average molecular weight 250).
[0039] Among the polyhydric alcohols of the defibrating agent (B1), from the standpoint of defibration ability and mechanical strength when formed into a molded product, at least one polyhydric alcohol selected from the group consisting of dipropylene glycol, triethylene glycol, diglycerol, tripropylene glycol, tetraethylene glycol, polyethylene glycol (number average molecular weight 200 to 400), polyoxypropylene glycol (number average molecular weight 200 to 400), and polyoxypropylene glyceryl ether (number average molecular weight 200 to 400) is preferred, and at least one polyhydric alcohol selected from the group consisting of dipropylene glycol, triethylene glycol, diglycerol, tripropylene glycol, tetraethylene glycol, polyoxypropylene glycol (number average molecular weight 200), polyoxypropylene glycol (number average molecular weight 400), polyoxypropylene glyceryl ether (number average molecular weight 250), and polyoxypropylene glycol (number average molecular weight 400) is more preferred.
[0040] Among these, at least one polyhydric alcohol selected from the group consisting of dipropylene glycol, tripropylene glycol, polyoxypropylene glycol (average molecular weight 200) and polyoxypropylene glyceryl ether (average molecular weight 250) is particularly preferred from the standpoint of defibration ability.
[0041] The polyhydric alcohol used as the defibrating agent (B1) has a flash point of 100° C. or higher, and is therefore preferable from the standpoint of disaster prevention and safety during the production of the composition of the present invention.
[0042] The defibrating agent (B1) can be a lactone having a molecular weight of 86 to 115. Among these, δ-valerolactone and ε-caprolactone are preferred in terms of defibrating ability and safety in use.
[0043] If a large amount of the defibrating agent (B1) remains in the fiber-reinforced resin composition, the strength properties of a molded body using this resin composition as a molded body material tend to decrease, so it is preferable to remove the defibrating agent (B1) remaining in the resin composition from the molded body material or molded body.
[0044] The defibrating agent (B1) (a polyhydric alcohol having a molecular weight of 130 to 400 and a lactone having a molecular weight of 86 to 115) can be removed easily and preferably by vaporizing and separating it from the molded body material or molded body by heating under reduced pressure (for example, to 125 to 280°C) because the boiling point of the defibrating agent (B1) at room temperature and normal pressure is approximately 290°C or less.
[0045] The above dipropylene glycol, tripropylene glycol, polyoxypropylene glycol (average molecular weight 200), polyoxypropylene glyceryl ether (average molecular weight 250) and polyoxypropylene glycol (average molecular weight 400) each have structural isomers, and these isomers or mixtures thereof are also included in the defibrating agent (B1) of the present invention.
[0046] The defibrating agent (B1) has defibrating ability in a smaller amount than existing defibrating agents, such as ε-caprolactam (about one-third the amount of ε-caprolactam used by mass). In addition, by using it in combination with an existing defibrating agent (e.g., ε-caprolactam), it can exhibit a superior effect to existing defibrating agents (e.g., ε-caprolactam). For this reason, in the present invention, an existing defibrating agent (e.g., ε-caprolactam) can be used in combination with the defibrating agent (B1).
[0047] The defibrating agent (B2) is used in combination with the defibrating agent (B1) to improve defibration properties. The defibrating agent (B2) may be at least one filler selected from the group consisting of talc, clay, zeolite, aluminum oxide, calcium carbonate, titanium oxide, silica, magnesium oxide, and mica.
[0048] The defibrating raw material can be defibrated more easily by further adding a defibrating agent (B2) to the raw material of the fiber reinforced resin composition. The defibrating agent (B2) may be used by adding it to the defibrating raw material simultaneously with the defibrating agent (B1), or before or after the defibrating agent (B1).
[0049] When the defibrating agent (B2) is added, the blending ratio of the defibrating agent (B2) is 0.01 to 1.0 part by mass, and preferably 0.01 to 0.6 part by mass, per 1 part by mass of the defibrating agent (B1).
[0050] Among the defibrating agents (B2), talc and clay are preferred from the viewpoint of ease of handling and effectiveness. Talc having an average particle size of 1 to 13 μm can be suitably used. When the average particle size is within this range, the strength properties of the molded body are further improved. Surface-treated and non-surface-treated talc are commercially available, but surface-treated talc, particularly aminosilane-treated talc, is preferred. If talc and the defibrating agent (B1) are mixed in advance and then added to the defibrating raw material, the impact resistance of the resulting molded body is improved.
[0051] 3. Fiber-reinforced resin composition The fiber-reinforced resin composition of the present invention is a resin composition (D) containing microfibrillated hydrophobic cellulosic fibers (A), a defibrating agent (B1), a thermoplastic resin (C), and optionally a defibrating agent (B2). The defibrating agents (B1) and (B2) are as described above.
[0052] The microfibrillated cellulose fiber contained in the resin composition of the present invention is a microfibrillated hydrophobized cellulose fiber (hydrophobized MFC) from the viewpoint of dispersibility and defibration in the resin. In this hydrophobized MFC, the hydrogen atoms of some of the hydroxyl groups of the sugar chains constituting the cellulose fiber of the MFC are preferably modified with an acyl group having 2 to 5 carbon atoms from the viewpoint of ease of production and dispersibility in the resin composition. Specific examples of such acyl groups include an acetyl group, an ethylcarbonyl group, an n-propylcarbonyl group, and a pivaloyl group. Among these acyl groups, MFC modified with an acyl group selected from the group consisting of an acetyl group, an ethylcarbonyl group, and a pivaloyl group is preferable because it has particularly good thermal stability and good dispersibility in the fiber-reinforced resin composition. Among them, an acetyl group is most preferable from the viewpoint of ease of production and production cost.
[0053] Two or more types of chemically modified MFCs can be combined (used together) and contained in the fiber-reinforced resin composition of the present invention. By using two types of chemically modified MFCs together, these chemically modified MFCs can be well dispersed in the fiber-reinforced resin composition.
[0054] When the fiber reinforced resin composition (D) contains a defibrating agent (B2), the content of the defibrating agent (B2) can be, for example, 0.1 to 10 mass%, preferably 1 to 7 mass%, and more preferably 2 to 6 mass%, relative to the total mass of the thermoplastic resin. When the fiber-reinforced resin composition (D) contains components other than the hydrophobized MFC (A), the defibrator (B1), the defibrator (B2), the thermoplastic resin (C), and the compatibilizer (E), the content of the other components can be, for example, 0.0001 to 20 mass%, and preferably 0.01 to 10 mass%, relative to the total mass of the composition.
[0055] The raw materials and production method of the chemically modified MFC and the details of the resin composition of the present invention (such as composition ratio) will be described later.
[0056] 4. Fiber raw material (fibrillating raw material) used in the composition of the present invention The fiber raw material used in the composition of the present invention is a hydrophobized cellulosic fiber aggregate (AcylCP) in which some of the hydrogen atoms of the hydroxyl groups in the sugar chains constituting the cellulosic fibers, or in the sugar chains and lignin, have been substituted with specific acyl groups.
[0057] For the preparation of AcylCP, cellulosic fiber assemblies derived from plants, microorganisms, algae, or tunicates (ascidians) can be used. Among these, plant-derived cellulosic fiber assemblies are preferred because they are readily available in large quantities. Examples of raw materials for plant-derived cellulosic fiber assemblies include wood, bamboo, hemp, jute, kenaf, cotton, beet, agricultural waste, waste paper, and woven fabrics. Among these, wood-derived cellulosic fiber assemblies (also called wood pulp) are preferred because they are readily available.
[0058] Wood pulp includes those that do not contain lignin and those that contain lignin (called lignopulp). Either of these can be used to produce defibration raw material. From the viewpoint of production costs, lignopulp is preferred.
[0059] Examples of wood that can be used as a raw material for wood pulp include wood derived from conifers such as Sitka spruce, pine (such as Abies sachalinensis and Japanese red pine), cedar, and cypress, and wood derived from broad-leaved trees such as eucalyptus and acacia. Plant-derived pulp obtained from these is preferably used for producing defibrating raw materials.
[0060] Furthermore, among coniferous pulps, lignopulp obtained from Japanese larch, red pine, or cedar is preferred because by incorporating chemically modified MFC produced using it, a fiber-reinforced resin composition with excellent strength properties can be obtained.
[0061] Wood pulp can be obtained by treating a plant raw material by a method such as mechanical pulping, chemical pulping, or a combination of mechanical and chemical pulping. Examples of such pulp include kraft pulp and mechanical pulp (MP). Examples of kraft pulp include softwood unbleached kraft pulp (NUKP), softwood oxygen-bleached unbleached kraft pulp (NOKP), and softwood bleached kraft pulp (NBKP). Examples of mechanical pulp include groundwood pulp (GP), refiner GP (RGP), thermomechanical pulp (TMP), and chemithermomechanical pulp (CTMP). In addition, deinked waste paper, cardboard waste paper, magazines, copy paper, and the like can also be used as pulp. One type of pulp may be used alone, or two or more types may be mixed and used. Wood pulp contains lignocellulose and is mainly composed of cellulose, hemicellulose, and lignin. In this specification, pulp from which lignin has not been completely removed and which still contains even a small amount of lignin is referred to as lignopulp, so pulp obtained by the above-mentioned various pulping methods and containing detectable lignin even in small amounts is included in lignopulp.
[0062] Lignopulp is advantageous in terms of production cost because it requires fewer production steps, has a good yield from raw materials (e.g., wood), requires fewer chemicals, and can be produced with less energy than lignin-free cellulose fibers or pulp. Therefore, lignopulp can be advantageously used in the present invention. The amount of lignin contained can be quantified by the Klason method.
[0063] In the present invention, wood pulp can be used that has been previously subjected to processes such as defibration, beating, and defibration using a refiner or a beater, or a combination of these, and that has a Canadian Standard Freeness (CSF) value (freeness) after the process of 40 mL to 500 mL, preferably 40 mL to 300 mL, and more preferably 40 mL to 200 mL.
[0064] The cellulose-based fibers derived from microorganisms can be obtained, for example, from pulp derived from microorganisms obtained by removing proteins and other impurities from a mixture of cellulose fibers and bacteria recovered from a culture medium in which acetic acid bacteria are cultured. The cellulose-based fibers derived from microorganisms are usually composed of nano-level cellulose fibers intertwined in a mesh-like structure, and can be used as a raw material for hydrophobic cellulose fiber aggregates.
[0065] The defibrated raw material used in the present invention is characterized in that some of the hydrogen atoms of the hydroxyl groups of the sugar chains or the sugar chains and lignin constituting the cellulosic fibers are substituted with a specific acyl group A (i.e., an acyl group having 2 to 5 carbon atoms) to make the fibers more hydrophobic than before the substitution. In this specification, the substitution of some of the hydrogen atoms of the hydroxyl groups of the sugar chains or the sugar chains and lignin constituting the cellulosic fibers is also referred to as "chemical modification", and the substituent introduced in place of the hydrogen atoms of the hydroxyl groups is sometimes referred to as "chemically modified group". Details of this acyl group A are the same as those of the acyl group described in the microfibrillated hydrophobic cellulosic fibers contained in the composition of the present invention.
[0066] By selecting a specific acyl group A as a substituent for the hydrogen atoms of some of the hydroxyl groups in the defibrating raw material, not only does the defibrating raw material chemically modified with such a substituent have improved thermal stability, but it also becomes more susceptible to microfibrillation during defibration processing by the defibrating agent used in the present invention, and is easily defibrated into chemically modified MFC. This is thought to be because in the defibrating raw material, the hydrogen bonds between the hydroxyl groups originally present on the cellulosic fiber surface are partially lost by acylation, and the defibrating raw material becomes more susceptible to microfibrillation during defibration processing due to the action of the defibrating agent.
[0067] This chemically modified MFC is also hydrophobized by being chemically modified with a specific acyl group A, and therefore has a higher hydrophobicity than the original cellulosic fiber, and therefore has a high affinity with thermoplastic resins and is easily dispersed uniformly in the resin. Therefore, the molded article of the present invention produced from the composition containing the chemically modified MFC produced using the defibrating agent (B1) and thermoplastic fiber has excellent strength properties.
[0068] The substituent in the defibrating raw material is preferably the acyl group A. The cellulose-based fiber modified with the acyl group A and microfibrillated, which is produced by defibrating the defibrating raw material using a defibrating agent (B1) (this cellulose-based fiber is also referred to as "Acyl (A) MFC"), has high affinity with thermoplastic resins and can be uniformly dispersed in thermoplastic resins.
[0069] In addition, by selecting an acyl group A as a substituent in the defibrating raw material, the heat resistance of the defibrating raw material can be improved.
[0070] Furthermore, when preparing defibrated raw material modified with acyl group A, not only can the cellulose originally present in the raw pulp be chemically modified while maintaining its high crystallinity, but this high crystallinity can also be maintained in the Acyl(A)MFC produced by microfibrillating the above-mentioned defibrated raw material.
[0071] Specific examples of the acyl group A having 2 to 5 carbon atoms include an acetyl group, an ethylcarbonyl group, an n-propylcarbonyl group, and a pivaloyl group. These are preferred because the acylating agent used in the acylation is available at a lower cost than other acylating agents. Among these, the acetyl group is more preferred.
[0072] 5. Degree of substitution of the hydrophobized cellulose fiber assembly (hydrophobized CP) used in the present invention The degree of modification with acyl groups (also referred to as the degree of substitution or DS) in the hydrophobic cellulose fiber assembly used in the present invention is expressed as the degree to which the hydrogen atoms of the hydroxyl groups present in one unit (repeating unit) of the cellulose polymer that constitutes the cellulose fiber assembly are replaced by the above-mentioned substituents. When the hydrophobized cellulose fiber aggregate is a hydrophobized lignocellulose fiber aggregate, the degree of substitution can be calculated, for example, based on the description in paragraphs 0253 to 0261 of JP 2018-150414, by replacing "ASA" with an acyl group (e.g., an acetyl group) and "apparent mass" with "formula weight of unmodified lignocellulose (formula weight of repeating unit)."
[0073] When the cellulose fiber assembly is composed entirely of cellulose (in the case of cellulose), the repeating units are glucopyranose residues, and the number of hydroxyl groups per unit is three.
[0074] On the other hand, when the cellulosic polymer is lignocellulose, the lignocellulose contains hemicellulose and lignin in addition to cellulose. The number of hydroxyl groups in the xylose residues in the xylan and the galactose residues in the arabinogalactan contained in the hemicellulose is two, and the number of hydroxyl groups in the standard lignin residue is also two, which is less than three.
[0075] Therefore, the upper limit of the degree of substitution in a lignocellulose fiber assembly (lignopulp) is less than 3. The upper limit of this degree of substitution is about 2.7 to 2.8, depending on the contents of hemicellulose and lignin contained in the lignocellulose fiber (lignopulp).
[0076] As described above, although it depends on the content of hemicellulose or lignin in the cellulosic fiber assembly, the degree of substitution (DS) with acyl groups is preferably about 0.2 to 2.0 in both the hydrophobized cellulosic assembly (hydrophobized CP) used in the present invention and the chemically modified microfibrillated cellulosic fibers (chemically modified MFC) obtained by defibrating it. The degree of substitution (DS) is more preferably about 0.3 to 1.5, and even more preferably about 0.3 to 1.4. In particular, when the acyl group is an acetyl group, the degree of substitution (DS) is more preferably about 0.4 to 1.3.
[0077] A chemically modified MFC having a DS in the above range has an appropriate degree of crystallinity and SP (solubility parameter), and therefore disperses uniformly in a matrix (thermoplastic resin), and a melt-kneaded composition containing such a chemically modified MFC has excellent physical properties.
[0078] The degree of substitution (DS) can be analyzed by various analytical methods such as neutralization titration, FTIR, and two-dimensional NMR (1H and 13C-NMR).
[0079] 6. Fiber size and observation methods, etc. In the present invention, the microfibrillated cellulose fiber (MFC) does not only mean a fiber in which all the fibers constituting the above-mentioned cellulose fiber assembly are microfibrillated to the nano-order diameter, but also means a cellulose fiber that contains at least a microfibrillated portion, and refers to the above-mentioned cellulose fiber having a nano-order diameter or the diameter of the fibers inside or on the surface of the fiber being on the nano-order. This also applies to chemically modified MFC.
[0080] The fiber diameters of the microfibrillated cellulose fibers (MFC) and chemically modified microfibrillated cellulose fibers (chemically modified MFC) referred to in this specification are each about several tens of nm to several μm.
[0081] The fiber diameter and fiber length of MFC and chemically modified MFC can be measured by taking a scanning electron microscope (SEM) photograph at 500 to 10,000 times magnification. The average fiber diameter (average fiber diameter) and the average fiber length (average fiber length) can be calculated as the average value when measuring at least 50 or more MFC or chemically modified MFC within the field of view of the SEM.
[0082] When taking SEM photographs of the chemically modified MFC in a thermoplastic resin composite, it is preferable to dissolve the thermoplastic resin in the thermoplastic resin composite with a solvent in which the thermoplastic resin is soluble and the chemically modified MFC is insoluble (e.g., hexafluoroisopropanol for polyamide composites and polyester composites, dichloromethane for polycarbonate composites, and non-polar, high-boiling point hydrocarbons such as decalin and xylene for polyethylene composites and polypropylene composites), and then take SEM photographs of the remaining chemically modified MFC.
[0083] 7. Method for producing the hydrophobized cellulose fiber assembly (fibre raw material) used in the present invention The method for preparing defibrated raw materials (acylation reaction) will be explained.
[0084] The modification of the raw material pulp with an acyl group can be carried out by a known method, for example, by reacting the raw material pulp with an acylating agent having an acyl group in a solvent while stirring or while standing. Examples of the acylating agent include carboxylic acid anhydrides, carboxylic acid halides such as carboxylic acid chlorides, and vinyl carboxylates. Among these, vinyl carboxylates are preferred because by-products can be easily removed from the reaction system.
[0085] In chemical modification with acyl groups, by using the corresponding vinyl carboxylate (vinyl carboxylate) as the acylating agent, the coloring of the chemically modified cellulosic fiber obtained by acylation is reduced, and in turn, the coloring of the melt-kneaded composition (composite) prepared by compounding the same can be reduced.
[0086] Of course, it is also possible to use acylating agents other than vinyl carboxylates (e.g., carboxylic acid chlorides, carboxylic acid anhydrides). In this case, it is preferable to add an organic or inorganic base during the reaction to capture the acid (hydrochloric acid, carboxylic acid, etc.) that is by-produced in the acylation reaction. However, the salt that is produced is likely to be mixed into the acylated cellulose fiber, which may cause the target acylated cellulose fiber to become discolored, so in this case careful purification is required.
[0087] Among these acylating agents, it is preferable to use an acylating agent having an acyl group selected from the group consisting of an acetyl group, a propionyl group, and a pivaloyl group, since this makes it possible to produce acylated microfibrillated cellulose-based fibers having particularly good thermal stability.
[0088] Specific examples of the acylating agent having an acyl group include vinyl acetate, acetic anhydride, vinyl pivalate, and pivalic anhydride. Among these, acylating agents having an acetyl group (vinyl acetate and acetic anhydride) are preferred from the viewpoint of production costs.
[0089] The acylation reaction is preferably carried out in a solvent in the presence of a base. A solvent that does not react with the acylation agent, easily swells the acylation raw material, and can be easily removed from the reaction system after the reaction with the acylation raw material is preferred. Examples of such a solvent include polar aprotic solvents such as N-methylpyrrolidone (NMP), dimethylformamide (DMF), dimethylacetamide (DMAc), and dioxane. The amount of the solvent used is about 20 to 200 parts by mass per part by mass of the acylation raw material in a dry state.
[0090] However, when the acylating agent is liquid at the reaction temperature and the by-products produced by the reaction are also liquid, the acylating agent and the by-products can be used as a solvent. In this case, the amount of the solvent used is about 0 to 3 parts by mass per part by mass of the acylation raw material. For example, when acylation (i.e., acetylation) is performed using acetic anhydride as the acylating agent, the amount of the solvent used is about 0 (no solvent) to 3 parts by mass per part by mass of the acylation raw material.
[0091] Examples of the base include amines such as pyridine and dimethylaniline, alkali metal salts of acetic acid such as potassium acetate and sodium acetate, and alkali metal carbonates such as lithium carbonate, potassium carbonate and sodium carbonate. The amount of the base used is about 0.1 to 1 mole per mole of hydroxyl groups in the acylation raw material.
[0092] The amount of the acylating agent used relative to the raw material pulp can be appropriately adjusted depending on the moisture content of the raw material pulp, the desired degree of acylation (degree of substitution, DS), and the like.
[0093] The degree of acylation (degree of substitution, DS) during the acylation reaction can be determined by taking an amount required for analysis from the reaction mixture, removing unreacted acylating agent, acylation by-products, etc. by washing, extraction, etc., measuring the FTIR spectrum, and quantifying using a previously prepared calibration curve. Therefore, the reaction is stopped when the desired DS is reached, and the reaction mixture is subjected to normal purification procedures such as filtration, washing, extraction, etc., to obtain an acylated cellulose fiber assembly (acylated pulp) having the desired DS.
[0094] The amount of the acylating agent used is about 0.5 to 2 times the number of moles of hydroxyl groups present in the raw pulp. When the raw pulp contains water, it is preferable to use a larger amount of the acylating agent than the above, taking into account the amount of the acylating agent consumed by the water.
[0095] The reaction temperature is usually about 10 to 130°C, and preferably about 20 to 125°C.
[0096] The reaction time is usually about 2 to 24 hours when acylation of raw material pulp derived from wood, and usually about 4 to 100 hours when acylation of raw material pulp derived from a microorganism.
[0097] 8. Method for defibrating defibrated raw material and method for producing composition containing defibrated chemically modified nanofibrillated cellulose-based fibers The defibration of the defibration raw material can be carried out by adding the defibration raw material together with the defibration agent (B1) to a defibration medium (water or a mixed solvent of water and a water-soluble organic solvent, or an organic solvent in which the chemically modified cellulosic fibers and the thermoplastic resin to be compounded are insoluble), and then carrying out a defibration process such as stirring and kneading while the defibration raw material is dispersed in the defibration medium.
[0098] The amount of the defibrating raw material used in the defibrating treatment can be, for example, 1 to 30 mass %, and preferably 3 to 25 mass %, based on the total mass of the thermoplastic resin (C) in the thermoplastic resin composition (D).
[0099] The amount of the defibrating agent (B1) used in the defibrating treatment can be, for example, 0.5 to 5 parts by mass, and preferably 0.7 to 3 parts by mass, per 1 part by mass of the chemically modified cellulosic fibers.
[0100] The amount of the thermoplastic resin (C) used can be, for example, 3 to 100 parts by mass, preferably 4 to 30 parts by mass, and more preferably 10 to 30 parts by mass, per part by mass of the chemically modified cellulosic fibers.
[0101] The amount of the defibrating medium used in the defibrating treatment can be, for example, 0.5 to 10 parts by mass, and preferably 1 to 5 parts by mass, per 1 part by mass of the chemically modified cellulosic fibers.
[0102] When the defibrating agent (B2) is used in the defibrating treatment, the amount of the defibrating agent (B2) used can be, for example, 0.01 to 1 part by mass, and preferably 0.01 to 0.6 parts by mass, per 1 part by mass of the defibrating agent (B1).
[0103] When a compatibilizer (E) is used in the defibration treatment, the amount of the compatibilizer (E) used can be, for example, 0.5 to 5 parts by mass, and preferably 0.7 to 3 parts by mass, per part by mass of the chemically modified cellulosic fibers.
[0104] When a composite containing a resin and chemically modified cellulose-based fibers is produced by a melt kneading method, it is efficient to carry out the fiber defibration treatment using a single-screw or multi-screw kneader.
[0105] In addition, in the step of performing a melt kneading operation on a mixture of the defibrating raw material, the defibrating agent, and the thermoplastic resin to be compounded, the defibrating raw material can be defibrated in the molten thermoplastic resin. It is preferable to use a single-shaft or multi-shaft kneader for this melt kneading.
[0106] As the defibrating agent, a defibrating agent (B1) is used, but from the standpoint of strength characteristics, it is preferable to use the defibrating agent (B1) in combination with an inorganic filler, i.e., a defibrating agent (B2), rather than using only the defibrating agent (B1).
[0107] The defibrating agent (B1) used may be contained in the melt-kneaded resin composition, or may be removed from the resin composition. In terms of the strength properties of the molded product to be formed, it is preferable to remove the defibrating agent (B1) from the resin composition. However, it is not necessary to completely remove the defibrating agent (B1), and it is sufficient to remove it to the extent that it does not affect the physical properties of the resulting resin composition. Even if the amount of defibrating agent (B1) remaining in the resin composition is small, by analyzing and detecting it, it is possible to know that the resin composition was produced by the production method of the present invention, which is convenient for product tracing.
[0108] The amount of the defibrating agent (B1) remaining in the resin composition varies depending on the resin used, but is usually 0.001 to 2 mass%, and preferably 0.01 to 1 mass%, based on the total amount of the resin composition. Molded articles made of a resin composition containing this amount of defibrating agent (B1) have excellent strength properties.
[0109] Examples of the production method of the present invention relating to a resin composition containing chemically modified microfibrillated cellulose fibers (chemically modified MFC) include the following Methods I to III.
[0110] Method I is a method for producing a resin composition (D) containing microfibrillated hydrophobic cellulosic fibers (A) and a thermoplastic resin (C), which comprises a step of mixing a hydrophobic cellulosic fiber aggregate (AP), a defibrating agent (B1), and a thermoplastic resin (C), and defibrating and microfibrillating the cellulosic fiber aggregate (AP) during the mixing operation.
[0111] Specifically, the present invention relates to a method for producing a fiber-reinforced resin composition (D) containing microfibrillated hydrophobic cellulose-based fibers (A) and a thermoplastic resin (C), the method including a step of mixing a hydrophobic cellulose-based fiber assembly (AP) modified with an acyl group having 2 to 5 carbon atoms, a defibrating agent (B1), and a thermoplastic resin (C), and defibrating and microfibrillating the hydrophobic cellulose-based fiber assembly (AP) during the mixing operation, in which the microfibrillated hydrophobic cellulose-based fibers (A) are modified with an acyl group having 2 to 5 carbon atoms, and the defibrating agent (B1) is at least one compound selected from the group consisting of polyhydric alcohols having a molecular weight of 130 to 400 and lactones having a molecular weight of 86 to 115.
[0112] Method II is a method in which a defibrating agent (B1), a hydrophobic cellulose fiber aggregate (AP), and a thermoplastic resin (C) are mixed, the hydrophobic cellulose fiber aggregate is defibrated and composited, and then the defibrating agent (B1) is removed to produce a resin composition (D) containing microfibrillated hydrophobic cellulose fibers (A) and a thermoplastic resin (C).
[0113] For more details, (1) a first step of mixing a hydrophobized cellulose fiber assembly (AP) modified with an acyl group having 2 to 5 carbon atoms, a defibrating agent (B1) and a thermoplastic resin (C) and defibrating the hydrophobized cellulose fiber assembly (AP) during the mixing operation to form microfibrils; (2) a second step of removing the defibrating agent (B1) from the mixture obtained in the first step, which contains the microfibrillated hydrophobized cellulosic fibers (A), the defibrating agent (B1), and the thermoplastic resin (C); A method for producing a fiber-reinforced resin composition (D) containing microfibrillated hydrophobized cellulosic fibers (A) and a thermoplastic resin (C), comprising: The method for producing a fiber-reinforced resin composition (D) is such that the microfibrillated hydrophobic cellulosic fibers (A) are modified with an acyl group having 2 to 5 carbon atoms, and the defibrating agent (B1) is at least one compound selected from the group consisting of polyhydric alcohols having a molecular weight of 130 to 400 and lactones having a molecular weight of 86 to 115.
[0114] Method III is a method in which a hydrophobic cellulose fiber aggregate (AP) modified with acyl groups having 2 to 5 carbon atoms is defibrated and then composited with a thermoplastic resin (C) to produce a resin composition containing microfibrillated hydrophobic cellulose fibers (A) and a thermoplastic resin (C).
[0115] For more details, (1) a first step of producing microfibrillated hydrophobic cellulose fibers (A) by defibrating a hydrophobic cellulose fiber assembly (AP) modified with an acyl group having 2 to 5 carbon atoms using a defibrating agent (B1); and (2) A second step of mixing the microfibrillated hydrophobic cellulosic fibers (A) obtained in the first step with a thermoplastic resin (C). The present invention relates to a method for producing a fiber-reinforced resin composition (D) containing microfibrillated hydrophobized cellulosic fibers (A) and a thermoplastic resin (C), the method comprising the steps of:
[0116] The defibration and microfibrillation of the defibrated raw material in the above-mentioned Method III can be carried out, for example, by making the defibrated raw material into a suspension or slurry and using known means such as mechanical grinding or beating using a refiner, high-pressure homogenizer, grinder, single-shaft or multi-shaft kneader (preferably a multi-shaft kneader), bead mill, etc. In the above-mentioned Method III, if the defibration and microfibrillation of the defibration raw material is carried out in a single-screw or multi-screw kneader in the first step, and the mixing in the second step is carried out in the single-screw or multi-screw kneader used in the first step, the fiber-reinforced resin composition (D) can be produced efficiently using one type of equipment.
[0117] Among the above-mentioned manufacturing methods, Method I and Method II are useful because they allow for a simple procedure of mixing the defibrating raw material, the defibrating agent (B1) and the thermoplastic resin (C) and defibrating the defibrating raw material during the melt-kneading to obtain a resin composition (D) containing hydrophobic MFC (microfibrillated hydrophobic cellulosic fiber (A)).
[0118] The resin composition (D) of the present invention contains microfibrillated hydrophobic cellulosic fibers ((A); hydrophobic MFC) that have excellent dispersibility in the resin and that have been easily defibrated from the defibrating raw material by the defibrating agent (B1). In terms of ease of production and dispersibility in the resin composition, it is preferable that the hydrogen atoms of some of the hydroxyl groups in the sugar chains constituting the cellulosic fibers of the MFC be modified with acyl groups having 2 to 5 carbon atoms in the hydrophobic MFC. Specific examples of such acyl groups include acetyl, ethylcarbonyl (also called propionyl), n-propylcarbonyl (also called butanoyl) and pivaloyl. Among these acyl groups, the modified MFCs with acyl groups selected from the group consisting of acetyl, ethylcarbonyl and pivaloyl groups have particularly good thermal stability and good dispersibility in the fiber-reinforced resin composition. Among these, the acetyl group is the most preferred from the viewpoints of ease of production and production cost. Two or more types of chemically modified MFCs can be combined (used in combination) and contained in the fiber reinforced resin composition of the present invention. By using two or more types of chemically modified MFCs in combination, these chemically modified MFCs can be well dispersed in the fiber reinforced resin composition.
[0119] In the step of mixing the hydrophobized cellulose fiber aggregate or the microfibrillated hydrophobized cellulose fiber with the resin described in any one of Methods I to III above, it is preferable to further mix a compatibilizer (E).
[0120] By mixing a compatibilizer, the mixing state between the chemically modified MFC and the thermoplastic resin, particularly the highly hydrophobic thermoplastic resin (e.g., polypropylene, polyethylene, etc.), is improved, and thus the strength properties of the molded article of the present invention containing these thermoplastic resins are improved.
[0121] As the compatibilizer, it is preferable to use a polymeric compound having a hydrophobic polymer and a hydrophilic group or hydrophilic fragment. Specific examples of such polymeric compounds include maleic anhydride-modified polypropylene, maleic anhydride-modified polyethylene, and block polymers consisting of hydrophobic fragments and hydrophilic fragments. Examples of block polymers consisting of hydrophobic fragments and hydrophilic fragments include block polymers consisting of resin affinity segment A and cellulose affinity segment B disclosed in JP 2014-162880 A.
[0122] When the fiber-reinforced resin composition (D) of the present invention contains a compatibilizer (E), the content of the compatibilizer in the composition can be, for example, 0.1 to 5 parts by mass, and preferably 0.5 to 5 parts by mass, per part by mass of the chemically modified MFC (A) contained.
[0123] It is preferable to use both the defibrated raw material and the chemically modified MFC having a solubility parameter (SP value) of about 9.9 to 15, and preferably about 10 to 14.5.
[0124] In the above-mentioned manufacturing methods and the resin composition of the present invention, the thermoplastic resin used is preferably one or more kinds of thermoplastic resins. In particular, when manufacturing a composite containing a highly hydrophobic thermoplastic resin (e.g., polypropylene, polyethylene, etc.), it is preferable to use a thermoplastic resin (e.g., polylactic acid, polyamide 6, etc.) having an SP value larger than that of the highly hydrophobic thermoplastic resin and smaller than that of the chemically modified cellulose fiber used, in combination with the highly hydrophobic thermoplastic resin (e.g., polypropylene, polyethylene, etc.).
[0125] In particular, for example, when producing a composite containing polypropylene (whose SP value is 8.1) as a thermoplastic resin and chemically modified microfibrillated cellulose fibers having an SP value of about 14 (e.g., microfibrillated acetylated lignocellulose fibers having an SP value of about 14), it is preferable to use, for example, polylactic acid (whose SP value is 11.4) and / or polyamide 6 (whose SP value is 12.2) in combination with polypropylene.
[0126] As the resin used in the method for producing a composition containing fibers and a resin of the present invention, among various resins, a thermoplastic resin is preferably used because of its excellent productivity and versatility.
[0127] In each of the above-mentioned production methods, examples of thermoplastic resins that are preferably used include polyamide, polyolefin, aliphatic polyester, aromatic polyester, polyacetal, polycarbonate, polystyrene, acrylonitrile-butadiene-styrene copolymer (ABS resin), polycarbonate-ABS alloy (PC-ABS alloy), and modified polyphenylene ether (m-PPE).
[0128] The thermoplastic resin may be used alone or in combination of two or more kinds.
[0129] As the polyamide (PA), polyamide 6 (nylon 6, PA6), polyamide 66 (nylon 66, PA66), polyamide 610 (PA610), polyamide 612 (PA612), polyamide 11 (PA11), polyamide 12 (PA12), polyamide 46, polyamide XD10 (PAXD10), polyamide MXD6 (PAMXD6), etc. can be preferably used.
[0130] As the polyolefin, polypropylene (PP), polyethylene (PE, particularly high density polyethylene HDPE), copolymers of ethylene and propylene, and the like can be preferably used.
[0131] Furthermore, polyisobutylene (hereinafter also referred to as "PIB"), polyisoprene (hereinafter also referred to as "IR"), polybutadiene (hereinafter also referred to as "BR"), etc. can also be preferably used.
[0132] As the polypropylene (PP), isotactic polypropylene (iPP), syndiotactic polypropylene (sPP), etc. can be preferably used.
[0133] As the aliphatic polyester, polymers or copolymers of diols and aliphatic dicarboxylic acids such as succinic acid and valeric acid (e.g., polybutylene succinate (PBS)), homopolymers or copolymers of hydroxycarboxylic acids such as glycolic acid and lactic acid (e.g., polylactic acid, poly-ε-caprolactone (PCL), etc.), and copolymers of diols, aliphatic dicarboxylic acids, and the above-mentioned hydroxycarboxylic acids can be preferably used.
[0134] As the aromatic polyester, a polymer of a diol such as ethylene glycol, propylene glycol, 1,4-butanediol, etc. and an aromatic dicarboxylic acid such as terephthalic acid, etc., can be preferably used. Specifically, for example, polyethylene terephthalate (PET), polypropylene terephthalate (PPT), polybutylene terephthalate (PBT), etc. can be preferably used.
[0135] As the polyacetal (also called polyoxymethylene, POM), in addition to a homopolymer of paraformaldehyde, a copolymer of paraformaldehyde and oxyethylene can also be preferably used.
[0136] For polycarbonate (PC), a reaction product of bisphenol A or a bisphenol derivative thereof with phosgene or phenyl dicarbonate can be preferably used.
[0137] As polystyrene (PS), in addition to general-purpose PS (GPPS), PS (HIPS) in which a rubber component is dispersed in a PS matrix to improve impact resistance can be suitably used. In addition to polystyrene (PS), styrene copolymers (acrylonitrile-butadiene-styrene copolymers, ABS resins) are preferred resins as the matrix of the fiber-reinforced resin composition of the present invention.
[0138] A blend of polycarbonate (PC) and ABS (PC-ABS alloy) is excellent in impact resistance, weather resistance and moldability, and is therefore preferably used as the matrix of the resin composition in each of the above-mentioned production methods of the present invention.
[0139] A blend of PPE and PS (PPE-PS blend) is a type of modified polyphenylene ether (PPE) (m-PPE). The PPE-PS blend is preferred because it has high heat resistance and is lightweight.
[0140] In addition, examples of thermoplastic resins that can be used other than those mentioned above include polyvinyl chloride, polyvinylidene chloride, fluororesins, (meth)acrylic resins, (thermoplastic) polyurethanes, vinyl ether resins, polysulfone resins, and cellulose resins (e.g., triacetylated cellulose, diacetylated cellulose, acetylbutyl cellulose, etc.).
[0141] The thermoplastic resin and the chemically modified microfibrillated cellulosic fibers are preferably composited by a melt kneading method.
[0142] The kneading process is a process in which a defibrating raw material (also called a chemically modified cellulose fiber aggregate or chemically modified pulp) is melt-kneaded with a thermoplastic resin, and the defibrating raw material is defibrated into chemically modified microfibrillated cellulose fiber (chemically modified MFC) in the molten thermoplastic resin, thereby producing a composition containing the chemically modified MFC and the thermoplastic resin.
[0143] When the melt-kneaded composition contains additives other than the defibrating agent, it is preferable to add them in the mixing process of the raw materials to be melt-kneaded or in this melt-kneading process, and melt-knead both the defibrating material and the thermoplastic resin.
[0144] The melt-kneaded composition can be produced by melt-kneading a thermoplastic resin, the defibrating raw material, the defibrating agent, and, if necessary, additives.
[0145] The heating temperature can be adjusted according to the melting point of the thermoplastic resin used. The heating temperature is preferably about ±10°C above the minimum processing temperature recommended by the thermoplastic resin supplier. By setting the heating temperature within this temperature range, the chemically modified MFC and the thermoplastic resin can be mixed uniformly.
[0146] The melt-kneading time may be adjusted within the range recommended by the kneader manufacturer, taking into consideration the production volume, and the operating conditions such as the performance and rotation speed of the device. A shorter heating time is preferable because it can prevent deterioration of the molten kneaded product due to heat and oxidation.
[0147] In order to prevent deterioration due to heating and oxidation during melt kneading, it is preferred to add an additive such as an antioxidant and to perform the kneading in a nitrogen atmosphere.
[0148] As the kneader, a single-shaft or multi-shaft kneader can be preferably used. The higher the rotation speed of the single-shaft or multi-shaft kneader used, the easier it is for the chemically modified pulp to be microfibrillated during the melt-kneading step, so this is preferred.
[0149] In this melt-kneading process, the chemically modified pulp is defibrated and microfibrillated by the shear stress during kneading and the action of the defibrating agent, and the resulting chemically modified microfibrillated cellulose-based fibers are well dispersed in the thermoplastic resin with the aggregation of the fibers suppressed.
[0150] In this kneading step, the chemically modified pulp having a fiber diameter of several tens of μm to several hundreds of μm is defibrated into chemically modified microfibrillated cellulosic fibers having a fiber diameter of several tens of nm to several μm during kneading.
[0151] The defibrating raw material can be defibrated and combined with the thermoplastic resin by the action of the defibrating agent and the shear stress of the melt kneader during melt kneading with the thermoplastic resin. Therefore, the melt kneading method simplifies the manufacturing process and reduces the manufacturing cost.
[0152] It is also possible to mix the chemically modified cellulose fiber aggregate (also called chemically modified pulp or defibrated raw material) and the thermoplastic resin before melt-kneading them. For example, (i) dry chemically modified MFC or chemically modified pulp can be mixed with powdered or granular thermoplastic resin, and the resulting mixture can be supplied to the kneader. Alternatively, (ii) chemically modified pulp and powdered or granular thermoplastic resin can be dispersed in a dispersion liquid in which they are not soluble, mixed, and then dried and supplied to the kneader. As a mixing means, it is preferable to use a bench roll, a Banbury mixer, a kneader, a planetary mixer, a Henschel type mixer, a stirrer with stirring blades, or a revolution or rotation type stirrer.
[0153] When the chemically modified pulp and the powdered or granular thermoplastic resin are dispersed in a dispersion liquid in which they are not soluble and then mixed, it is preferable to use a wet media-type attritor or a wet fine grinder Trigonal, because this makes it possible to simultaneously defibrate and disperse the chemically modified pulp and mix the chemically modified pulp with the thermoplastic resin.
[0154] As in (i) above, when the dry chemically modified pulp and the powdered or granular thermoplastic resin are mixed in advance before melt kneading, it is also possible to add additives during this mixing.
[0155] The content of the chemically modified microfibrillated cellulose fiber (chemically modified MFC) (A) in the melt-kneaded composition produced by the production method of the present invention is usually about 1 to 40 mass% and preferably 3 to 30 mass% based on the total mass of the thermoplastic resin (C) and the chemically modified MFC (A). The content of the thermoplastic resin (C) in the melt-kneaded composition is usually about 60 to 99 mass% and preferably 70 to 97 mass% based on the total mass of the resin (C) and the chemically modified MFC (A). By setting the content of the chemically modified MFC in the above range, a melt-kneaded composition having excellent strength properties can be obtained.
[0156] The melt-kneaded composition produced by the production method of the present invention can also be used as a masterbatch. When used as a masterbatch, the content of the chemically modified MFC (A) is preferably about 10 to 40 mass% based on the total mass of the thermoplastic resin (C) and the chemically modified MFC (A).
[0157] The composition produced by the production method of the present invention is preferably a composition in which a thermoplastic resin and a chemically modified MFC are melt-kneaded. The melt-kneading method is more productive than the method of impregnating a nonwoven fabric with a resin or resin precursor solution and a cellulose-based fiber to produce a composite, so that the production method of the present invention can produce a resin composition containing a chemically modified MFC with high productivity.
[0158] The fiber-reinforced resin composition of the present invention may contain additives within the range in which the effects of the present invention are not impaired. Examples of additives include compatibilizers, surfactants, starches, polysaccharides such as alginic acid, natural proteins such as gelatin, glue, and casein, tannins, zeolites, ceramics, inorganic compounds such as metal powder, colorants, plasticizers, pigments, antistatic agents, ultraviolet absorbers, and antioxidants.
[0159] 9. Molded body The melt-kneaded composition produced by the production method of the present invention can be used to produce the molded article of the present invention. When producing the molded article, the melt-kneaded composition can be processed into various shapes such as pellets, powder, sheet, plate, film, etc., and used as a molding material.
[0160] Examples of the molding method include injection molding, mold molding, extrusion molding, etc. Examples of the shape of the molded product include sheet-like, plate-like, film-like, three-dimensional structure, etc. Molded products of various shapes according to the application can be manufactured by the above molding method. By using the melt-kneaded composition manufactured by the manufacturing method of the present invention, a molded product having excellent strength properties can be obtained.
[0161] Molded articles produced from the melt-kneaded composition produced by the production method of the present invention can be used in fields that require mechanical strength (tensile strength, etc.).Specifically, they can be effectively used as interior materials, exterior materials, structural materials, etc. of transportation equipment such as automobiles, trains, ships, and airplanes; housings, structural materials, internal parts, etc. of electrical appliances such as personal computers, televisions, telephones, and watches; housings, structural materials, internal parts, etc. of mobile communication equipment such as mobile phones; housings, structural materials, internal parts, etc. of portable music playback equipment, video playback equipment, printing equipment, copying equipment, sports equipment, etc.; building materials; office equipment such as stationery, containers, etc. EXAMPLES
[0162] The present invention will be described in more detail below with reference to Examples, Comparative Examples and Test Examples, but the present invention is not limited to these Examples.
[0163] The meanings of the abbreviations used in the Examples, Comparative Examples, and Test Examples are as follows: Ac: Acetyl group NBKP: Bleached softwood kraft pulp TUKP: Unbleached kraft pulp from Todomatsu GP: Groundwood pulp AcNBKP: NBKP in which some of the hydrogen atoms of the hydroxyl groups have been replaced with acetyl groups. AcTUKP: TUKP in which some of the hydrogen atoms of the hydroxyl groups have been replaced with acetyl groups. TUKPAcGP: GP in which some of the hydrogen atoms of the hydroxyl groups have been replaced with acetyl groups. MI: Melt index (also called melt flow rate) DPG: Dipropylene glycol TEG: Triethylene glycol TPG: Tripropylene glycol PEG200: Polyethylene glycol with a number average molecular weight of 200 PPG200: Polyoxypropylene glycol with a number average molecular weight of 200 GP250: Polyoxypropylene glyceryl ether with a number average molecular weight of 250 PPG400: Polyoxypropylene glycol with a number average molecular weight of 400 PPG1000: Polyoxypropylene glycol with a number average molecular weight of 1000
[0164] Furthermore, the following terms used in the examples, comparative examples, figures, and tables have the following meanings. · Pass: The number of times the material to be processed (test material) is fed into the twin-screw kneader and put through the kneader is called a "pass." Therefore, for example, "1 pass" means that the material is put through the kneader once, "1st pass" means that the test material is put through the kneader for the first time (as the first time), and "2nd pass" means that the material that has been put through the kneader once is then put through the kneader for the second time. · Extrusion: This means feeding the material to be treated (test material) into a kneading machine (also called an extruder) and carrying out the kneading process.
[0165] (A) Raw materials used In the following Production Examples, Examples and Comparative Examples, the following raw materials were used. (1) Resin Polypropylene (hereinafter referred to as "PP"): Made by Japan Polypropylene, Novatec MA04A, MI=40, pellets Polypropylene powder (hereinafter referred to as "PP powder"): Made by Japan Polypropylene, Novatec MA04A, MI=40, powder form (2) Compatibilizer Maleic acid modified polypropylene (hereinafter referred to as "MAPP"): Toyobo, Toyo Tac H1000P, MI=110, powder (3) Filler Talc: Made by Nippon Talc, Microace MSZ-C, average particle size 12.8μm, amino-based surface treatment (4) Additives Antioxidant (hereinafter referred to as "AO"): BASF, Irganox 1010, phenolic antioxidant
[0166] (B) Equipment used Twin-screw kneader: Technobel, screw diameter φ15mm, L / D45 (L / D is the ratio of screw length (L) to screw diameter (D)) Injection molding machine: Nissei Plastics, NPX 7 type, clamping force 7 tons
[0167] (C) Test method and equipment used (1) Microscopic observation of cellulosic fibers (hereinafter simply referred to as "fibers") The state of the fibers, or the defibrated or dispersed state of the fibers in the composition was observed with an electron microscope as follows.
[0168] (1-1) Observation of the defibrillation state of fibers in a fiber-reinforced resin composition using a scanning electron microscope (a) Preparation of specimen for observation Sample preparation of fiber-reinforced resin composition (composition containing fiber, PP and MAPP) Using xylene as an extraction solvent for the resin components, the resin components (PP and MAPP) were extracted and removed from the fiber-reinforced resin composition to prepare a sample. Specifically, the fiber-reinforced resin composition (PP / MAPP / AO / fiber composite) was placed in the extraction solvent and heated at 140°C for about 2 hours to extract and remove the resin components, obtaining an extraction residue mainly composed of fibers. This was washed with ethanol, and the obtained fibers were placed on a copper plate and dried, after which they were coated with platinum using a sputtering device (JEOL SEC-3000FC Auto Fine Coater), and this was used as a sample for observation. (b) Observation The obtained observation samples were subjected to secondary electron image observation using a field emission scanning electron microscope (JSM-7800F: JEOL).
[0169] (2) Strength test (three-point bending test) Manufacturing method of test piece (molded body) A rectangular test piece (10 mm x 80 mm x 4 mm) was prepared using an injection molding machine. The cylinder temperature of the injection molding machine was set to 170°C (feeding section) to 190°C (measuring section) to melt the resin composition, which was then injected into a mold at a temperature of 35°C to prepare a molded body. The obtained test piece was left to stand for 2 days in an atmosphere at a temperature of 23°C and a relative humidity of 50%, and then tested. Testing Method The test pieces were subjected to strength tests using a universal testing machine (Shimadzu Corporation, AG5000E type) under the test conditions of a support distance of 64 mm and a test speed of 10 mm / min.
[0170] (3) Izod impact test A rectangular test piece (10mm x 80mm x 4mm) was prepared using an injection molding machine, and an Izod impact test was carried out using an Izod impact tester (manufactured by Toyo Seiki Seisakusho Co., Ltd.). A 2mm deep notch was inserted in the center of the test piece. The notch side was struck with a 2.75J hammer, causing a crack to develop from the notch, and the impact strength was calculated.
[0171] (4) Charpy impact test: Rectangular test pieces (10mm x 80mm x 4mm) were prepared using an injection molding machine, and a Charpy impact test was carried out using a Charpy impact tester (manufactured by Yasuda Seiki Seisakusho Co., Ltd.). A notch 2mm deep was inserted in the center of the test piece. A 2.0J hammer was used to strike the side opposite the notch, and the impact strength was calculated.
[0172] <Production Example 1> Production of AcTUKP ( Lot number: KA089, DS: 0.63 ) Pulp used: Unbleached kraft pulp (TUKP) derived from Japanese oak The TUKP was refined to obtain TUKP with a CSF of 300 ml, which was then paper-made to obtain a sheet-like TUKP with a thickness of approximately 0.2 mm. TUKP components (mass%): cellulose (65.4%), hemicellulose (31.6%), lignin (3.0%). Solid content: 10.2 mass%. Manufacturing method of AcTUKP: 4800g of acetic anhydride was added to the above sheet-form TUKP (solid content 2400g) and reacted at 125℃ for 6 hours. The reaction mixture was cooled to 50℃, the liquid was removed by decantation, and then heated to 80℃ under reduced pressure, and further heated to 50℃ in a vacuum dryer to distill off acetic anhydride and acetic acid. After drying, sheet-form AcTUKP with a dry weight of 2398g was obtained. The DS of this AcTUKP was 0.63. This AcTUKP was used in the defibration test described below.
[0173] Thereafter, the acetylated pulps shown in Table 1 were produced in the same manner as above.
[0174] [Table 1]
[0175] Example 1 Manufacture of fiber reinforced resin composition (Test No. PP1480, composition ratio: AcTUKP / MAPP / talc / AO / PP=(10 / 10 / 5 / 1 / 75)) All raw materials other than PP were mixed in the following composition ratio: AcTUKP (lot number KA091) / MAPP / talc / δ-valerolactone / water / AO = (1.94+10) / 10 / 5 / 10 / 20 / 1 to prepare a mixture. This mixture was used as the starting material to produce the titled fiber reinforced resin composition according to the following steps (1st pass to 3rd pass). Composition ratio notation: The numerical values in the composition ratio of the mixture fed to the twin-screw kneader, AcTUKP / MAPP / talc / δ-valerolactone / water / AO=(1.94+10) / 10 / 5 / 10 / 20 / 1, have the following meanings. (1.94+10): represents the mass ratio of AcTUKP in the total mass of the mixture. Here, the 1.94 in the above (1.94+10) means the mass ratio of the total of the acetyl group (Ac) of AcTUKP (calculated from the DS value of AcTUKP) and lignin in the total mass of the mixture. Also, the 10 in the above (1.94+10) means the mass ratio of the fiber component (i.e., cellulose + hemicellulose) in the total mass of the mixture. Therefore, (1.94+10)=11.94 is the mass ratio of AcTUKP in the total mass of the mixture. 10: Mass ratio of MAPP in the total mass of the mixture 5: Mass ratio of talc in the total mass of the mixture 10: Mass ratio of δ-valerolactone in the total mass of the mixture 20: Mass fraction of water in the total mass of the mixture 1: Mass ratio of AO in the total mass of the mixture Unless otherwise specified, the composition ratios of mixtures and kneaded products will be described in accordance with this notation method. The above method of describing the numerical values of the ratio of each component in the mixture is applied to the notation of the ratio of each component in the resin composition. However, for the components (composition ratio: 10 / 10 / 5 / 1 / 75) of the molded bodies (test pieces) shown in the tables showing the strength test results in this specification, the chemically modified fibers contained therein are indicated by their abbreviations (for example, acetylated unbleached Abies sachalinensis kraft pulp is indicated by the abbreviation AcTUKP), but the mass content is shown converted to that of unmodified fiber (i.e., the mass content of AcTUKP is converted to TUKP). Furthermore, when the contents of water and defibrating agent (B1) in the melt-kneaded product and molded body (test piece) are very small, the composition ratios of water and defibrating agent (B1) are omitted from the composition ratio of the melt-kneaded product.
[0176] The production method will be described in detail below. (1st pass: dehydration extrusion) The starting materials were dehydrated and extruded by passing them through a twin-screw kneader equipped with a vent and gradient-heating the kneader cylinder from 80°C (upstream) to 130°C (downstream). MAPP was swollen with δ-valerolactone (defibrator B1), and the mixture of the starting materials was kneaded and discharged in an integrated state.
[0177] (2nd pass: kneading δ-valerolactone / MAPP swollen material) The kneaded material that had passed through the first pass was passed through a twin-screw kneader with the kneader cylinder set at 130°C, and kneaded and extruded. Water and δ-valerolactone were discharged from the kneaded material that had passed through the first pass. The composition ratio of the kneaded material after the second pass was AcTUKP / MAPP / talc / (δ-valerolactone+water) / AO=(1.94+10) / 10 / 5 / 7.84 / 1 (total mass parts of the composition was 35.78).
[0178] (3rd pass: Dilution extrusion with PP) PP was mixed with the above-mentioned two-pass kneaded product to obtain a mixture with a composition ratio of (two-pass mixture) / PP=35.78 / 72.06, which was melt-kneaded in a twin-screw kneader with a cylinder temperature of 180°C, and degassed using a vacuum vent to reduce water and δ-valerolactone, to obtain a melt-kneaded product containing a small amount of water and 1 mass% or less of δ-valerolactone that does not significantly affect the strength properties of the fiber-reinforced composition produced. The composition ratio of the obtained melt-kneaded product was AcTUKP / MAPP / talc / AO / PP=(1.94+10) / 10 / 5 / 1 / 75 (AcTUKP converted to TUKP was 10 / 10 / 5 / 1 / 75). The melt-kneaded product contains a small amount of water and δ-valerolactone, which is a defibrating agent (B1), but since the composition ratio is small, the composition ratio of water and δ-valerolactone, which is a defibrating agent (B1), is omitted in the notation of the composition ratio.) This is also true for the fiber-reinforced resin compositions (melt-kneaded products) of Examples 2 to 11 below. The content of the defibrating agent (B1) in the fiber-reinforced resin compositions of Examples 2 to 11 was also 1 mass% or less.
[0179] Test pieces (molded bodies) were prepared from the obtained compositions according to the above conditions, and the test pieces were subjected to the three-point bending test, Izod impact test, and Charpy impact test according to the above methods. The results are shown in Table 2.
[0180] Example 2 Manufacture of fiber reinforced resin composition (Test No. PP1431, composition ratio: AcTUKP / MAPP / talc / AO / PP=(10 / 10 / 5 / 1 / 75)) The fiber-reinforced resin composition of Example 2 was obtained in the same manner as in Example 1, except that AcTUKP (lot number KA093 DS = 0.63) was used instead of AcTUKP (lot number KA091 DS = 0.61) and ε-caprolactone was used instead of the defibrating agent δ-valerolactone. Test pieces (molded bodies) were prepared from the obtained composition according to the above-mentioned conditions, and the test pieces were subjected to various tests in the same manner as in Example 1. The results are shown in Table 2. In addition, the fiber reinforced resin compositions in Tables 2 to 4 are
[0181] [Table 2]
[0182] (Examples 3 to 10) Examples 3 to 10 are examples in which fiber-reinforced resin compositions were produced by using a polyhydric alcohol as defibrating agent B1 in combination with talc as defibrating agent B2. The fibers used are as shown in the "Numbers of Examples and Comparative Examples Using Chemically Modified Pulp" column in Table 1. Test pieces (molded bodies) were prepared from the obtained compositions according to the above-mentioned conditions, and the test pieces were subjected to various tests in the same manner as in Example 1. The results are shown in Table 3.
[0183] Example 11 Except for not using talc, a fiber-reinforced resin composition was produced, a test piece (molded body) was prepared, and a test was performed in the same manner as in Example 6. The test results are shown in Table 3.
[0184] [Table 3]
[0185] A sample for microscopic observation was prepared from the obtained composition of Example 6 (Test No. PP1482) according to the above conditions, and the state of the fibers in the sample was observed under an electron microscope. The electron microscope image is shown in Figure 2. For comparison, only platinum coating was added to AcTUKP (KA091) used as the raw material for preparing the composition of Example 6, and the resultant was observed under an electron microscope. The electron microscope image is shown in Figure 1.
[0186] Comparing Figures 1 and 2, it can be seen that the fiber diameter of AcTUKP before melt-kneading was approximately 40 μm, but was defibrated to several tens of nm to 5 μm by kneading.
[0187] (Comparative Example 1) PP Molded Body (Non-Fiber Reinforced PP) Commercially available pelletized PP was processed into molded bodies (test pieces 10 mm wide x 80 mm long x 4 mm thick) using an injection molding machine at a cylinder temperature of 190°C. The obtained test pieces were subjected to the tests as described above, and the results are shown in Table 4.
[0188] (Comparative Example 2) Test No. PP1638 (same composition as Example 10 except that the number average molecular weight of PPG as the polyhydric alcohol is 1000) A fiber-reinforced resin composition was produced in the same manner as in Example 10, except that polyoxypropylene glycol having a number average molecular weight of 1000 (PPG1000) was used instead of polyoxypropylene glycol having a number average molecular weight of 400. A test piece (molded body) was produced from the obtained composition under the above-mentioned conditions, and the test piece was subjected to the above-mentioned method. The results are shown in Table 4.
[0189] (Comparative Example 3) Fiber-reinforced PP composition prepared without using a defibrating agent A test piece (molded body) was prepared from the AcNBKP (lignin 0.1%, DS=0.46)-containing PP composition (No. PP-304 composition) described in Table 11 of JP 2016-176052 A under the above-mentioned conditions, and the test piece was subjected to the above-mentioned method. The results are shown in Table 4. The method for producing this fiber-reinforced resin composition is as described in paragraphs 0276 to 0280 of JP 2016-176052 A.
[0190] (Comparative Example 4) Fiber-reinforced PP composition prepared without using a defibrating agent A test piece (molded body) was prepared from the AcGP (lignin 10.3%, DS=0.6)-containing PP composition (No. PP-450 composition) described in Table 11 of JP 2016-176052 A under the above-mentioned conditions, and the test piece was subjected to the above-mentioned method. The results are shown in Table 4. The method for producing this fiber-reinforced resin composition is as described in paragraphs 0276 to 0280 of JP 2016-176052 A.
[0191] [Table 4]
Claims
1. A fiber-reinforced resin composition (D) containing microfibrillated hydrophobized cellulosic fibers (A), a defibrating agent (B1), and a thermoplastic resin (C), the microfibrillated hydrophobic cellulosic fibers (A) are modified with an acyl group having 2 to 5 carbon atoms; The defibrating agent (B1) is at least one compound selected from the group consisting of tripropylene glycol and lactones having a molecular weight of 86 to 115. Resin composition (D).
2. The fiber reinforced resin composition (D) further contains a defibrating agent (B2), The fiber-reinforced resin composition according to claim 1, wherein the defibrating agent (B2) is at least one selected from the group consisting of talc, clay, zeolite, aluminum oxide, calcium carbonate, titanium oxide, silica, magnesium oxide, and mica.
3. The fiber-reinforced resin composition according to claim 1 or 2, wherein the defibrating agent (B1) is at least one selected from the group consisting of tripropylene glycol, δ-valerolactone, and ε-caprolactone.
4. The fiber-reinforced resin composition according to claim 1 or 2, wherein the microfibrillated hydrophobic cellulosic fibers (A) are modified with an acetyl group, and the defibrating agent (B1) is at least one selected from the group consisting of tripropylene glycol, δ-valerolactone, and ε-caprolactone.
5. The thermoplastic resin (C) is at least one selected from the group consisting of polyamide, polyolefin, aliphatic polyester, aromatic polyester, polyacetal, polycarbonate, polyvinyl chloride, polystyrene, acrylonitrile-butadiene-styrene copolymer (ABS resin), styrene-butadiene block copolymer, polycarbonate-ABS alloy (PC-ABS alloy) and modified polyphenylene ether (m-PPE). The fiber-reinforced resin composition according to any one of claims 1 to 4.
6. The fiber-reinforced resin composition according to claim 5, wherein the polyolefin is at least one selected from the group consisting of polypropylene, polyethylene, a polypropylene copolymer, and a polyethylene copolymer.
7. The fiber-reinforced resin composition according to any one of claims 1 to 6, wherein the microfibrillated hydrophobized cellulosic fiber (A) is a microfibrillated hydrophobized lignocellulosic fiber (MFLC).
8. The fiber reinforced resin composition according to any one of claims 1 to 7, wherein the content of the defibrating agent (B1) is 0.001 to 2 mass% based on the total mass of the fiber reinforced resin composition.
9. A molded article made of the fiber-reinforced resin composition according to claim 8.
10. The method includes a step of mixing a hydrophobized cellulose fiber assembly (AP) modified with an acyl group having 2 to 5 carbon atoms, a defibrating agent (B1), and a thermoplastic resin (C), and defibrating the hydrophobized cellulose fiber assembly (AP) during the mixing operation to form microfibrils. A method for producing a fiber-reinforced resin composition (D) containing microfibrillated hydrophobized cellulosic fibers (A) and a thermoplastic resin (C), comprising: the microfibrillated hydrophobic cellulosic fibers (A) are modified with an acyl group having 2 to 5 carbon atoms; The defibrating agent (B1) is at least one compound selected from the group consisting of tripropylene glycol and lactones having a molecular weight of 86 to 115. A method for producing a fiber-reinforced resin composition (D).
11. The production method according to claim 10, wherein a defibrating agent (B2) is further mixed in the step to produce a fiber-reinforced resin composition (D) further containing a defibrating agent (B2), wherein the defibrating agent (B2) is at least one selected from the group consisting of talc, clay, zeolite, aluminum oxide, calcium carbonate, titanium oxide, silica, magnesium oxide, and mica.
12. (1) a first step of mixing a hydrophobized cellulose fiber assembly (AP) modified with an acyl group having 2 to 5 carbon atoms, a defibrating agent (B1), and a thermoplastic resin (C), and defibrating the hydrophobized cellulose fiber assembly (AP) during the mixing operation to form microfibrils; (2) a second step of removing the defibrating agent (B1) from the mixture containing the microfibrillated hydrophobized cellulosic fibers (A), the defibrating agent (B1), and the thermoplastic resin (C) obtained in the first step; A method for producing a fiber-reinforced resin composition (D) containing microfibrillated hydrophobized cellulosic fibers (A) and a thermoplastic resin (C), comprising: the microfibrillated hydrophobic cellulosic fibers (A) are modified with an acyl group having 2 to 5 carbon atoms; The defibrating agent (B1) is at least one compound selected from the group consisting of tripropylene glycol and lactones having a molecular weight of 86 to 115. A method for producing a fiber-reinforced resin composition (D).
13. The production method according to claim 12, wherein a fiber-reinforced resin composition (D) further containing a defibrating agent (B2) is produced by further mixing a defibrating agent (B2) in the first step, wherein the defibrating agent (B2) is at least one selected from the group consisting of talc, clay, zeolite, aluminum oxide, calcium carbonate, titanium oxide, silica, magnesium oxide, and mica.
14. A method for producing a fiber-reinforced resin composition (D) containing microfibrillated hydrophobic cellulosic fibers (A), a thermoplastic resin (C), and a compatibilizer (E), or a method for producing a fiber-reinforced resin composition (D) containing microfibrillated hydrophobic cellulosic fibers (A), a defibrating agent (B2), a thermoplastic resin (C), and a compatibilizer (E), further comprising mixing a compatibilizer (E) in the step of claim 10 or 11 or the first step of claim 12 or 13.
15. The thermoplastic resin is at least one selected from the group consisting of polyamide, polyolefin, aliphatic polyester, aromatic polyester, polyacetal, polycarbonate, polystyrene, acrylonitrile-butadiene-styrene copolymer (ABS resin), polycarbonate-ABS alloy (PC-ABS alloy) and modified polyphenylene ether (m-PPE). The method for producing a fiber-reinforced resin composition (D) according to any one of claims 10 to 14.
16. A defibrating agent for defibrating a hydrophobic cellulose fiber assembly modified with an acyl group having 2 to 5 carbon atoms, the defibrating agent comprising at least one compound selected from the group consisting of tripropylene glycol and lactones having a molecular weight of 86 to 115.
17. The defibrating agent according to claim 16, wherein the compound is at least one selected from the group consisting of tripropylene glycol, δ-valerolactone, and ε-caprolactone.
Citation Information
Patent Citations
Method for producing aliphatic polyester composition, pulp used for the same, and cellulosic fiber, and method for microfibrillating the same
JP2005042283A
Process for production of aliphatic polyester composition, pulp to be used therein, and process for microfibrillation thereof
JP2007262649A
Method for producing cellulose nanofiber
JP2010216021A
Method for producing cellulose-containing thermoplastic resin, the cellulose-containing thermoplastic resin, and molded body of the same
JP2011219571A
Method for producing dispersion of fine cellulose fiber
JP2013036035A